Anchorage behavior of headed bars in reinforced concrete beams. (February 2021) - Abed, Huda Saad; Abed, Jasim Mohammed; Al-Rawe, Hesham Salim
Abstract: Nine simply supported reinforced concrete beams of dimensions 150 × 150 × 700 mm have been tested to study the anchorage behavior of installed headed bars. The variables included the size of the added head plate, debonded length and loading type. Therefore, four head areas 28*28, 32*32, 35*35 and 38*38 mm, three debonded lengths 0, 300 and 600 mm and two loading types (one-point load and two-point load) are used in this research. The test results of load failure values, type of failure and deflection for eight beams provided with plate head and one beam of the non-head bar are being obtained. It was found that the value of load failure increased with using higher plate head size and lower debonding length. Furthermore, the percentages of decrease in deflection for beams that have head net size Anh/Ab (2.9, 4, 5, and 6) are 29%, 36%, 38% and 44% respectively, and 12% and 55% when beams with debonding length 300 and 600 mm compared with beams of full bonded (zero debonded length). While the load failure for beams tested under two-points load was greater than beams which were tested under one-point load.